The Asymmetry Effect of Oil Consumption, Unemployment and Broadband Technology on Economic Growth in Indonesia - Rumbia, Wali Aya; Muthalib, Abd Azis; Abbas, Bakhtiar; Adam, Pasrun; Jabani, Asrul; Pasrun, Yuwanda Purnamasari; Muthalib, Dzulfikri Azis (International Journal of Energy Economics and Policy, 2022)
This research aims to examine the asymmetry effect of oil consumption, unemployment, and broadband technology on economic growth in Indonesia. Data on these attributes were annually collected from 2000 to 2019. The effect test result using the nonlinear autoregressive distributed lag (NARDL) model showed that oil consumption and unemployment affect economic growth asymmetrically in the long and short term. Meanwhile, broadband technology only affects economic growth only in the long term, and this effect is positive.